Rubber composition for golf ball core and golf ball
Patent Information
- Application Number
- JP2020216501
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-12-25
AI Technical Summary
【0014】 本発明のゴルフボールコア用ゴム組成物よれば、該ゴム組成物をゴルフボールのコアとして適用した場合に、ゴルフボールを打撃する際、コア内部のゴム架橋構造の特異な構造により該ゴアの破壊を防いで耐久性を改善することができる。
Smart Images

Figure 0007643038000005 
Figure 0007643038000001 
Figure 0007643038000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition for a golf ball core and a golf ball using the same, and in particular to a rubber composition for a golf ball that is suitably used as a core material for a golf ball consisting of one or more core layers and one or more cover layers, and a golf ball using the same. [Background technology]
[0002] Recently, two-piece solid golf balls and three-piece solid golf balls have become mainstream. These golf balls usually have a structure in which a core made of a rubber composition is covered with a single-layer or multi-layer cover made of various resin materials. The core occupies most of the volume of the golf ball and has a significant effect on the physical properties of the ball, such as resilience, hitting feel, and durability. Recently, various techniques have been proposed to realize a unique core hardness gradient by appropriately adjusting the cross-sectional hardness of the core, thereby improving the flight distance by optimizing the spin characteristics during full shots with a driver or iron.
[0003] In order to improve the durability of the core for golf balls, several techniques have been proposed for incorporating various resin components into the rubber composition for the core.For example, the four documents of U.S. Patent Nos. 6,120,390, 6,890,992, 6,332,850, and 6,919,395 (Patent Documents 1 to 4) describe techniques for blending resin components such as modified butadiene terpolymers, modified styrene terpolymers, nonionic modified polyolefins, and metallocene catalyst polymers into the base rubber of the core for golf balls.
[0004] In addition, Japanese Patent No. 4020634 (Patent Document 5) describes a rubber composition containing a ternary complex consisting of a rubber component, a polyolefin component, and a nylon component, and Japanese Patent No. 6366387 (Patent Document 6) describes a rubber composition containing an olefin-(meth)acrylic acid alkyl ester copolymer. In addition, Japanese Patent No. 6408811 (Patent Document 7) describes blending at least one selected from the group consisting of C9-based petroleum resins and C5C9-based copolymerized petroleum resins into a rubber composition, and Japanese Patent Laid-Open No. 2020-103339 (Patent Document 8) describes blending a terpene resin into a rubber composition.
[0005] Other technical documents have proposed a technique of compounding a resin component into a rubber composition to improve moldability. For example, Japanese Patent No. 6180722 (Patent Document 9) describes a technique of adding a low melting point polymer to the rubber composition for the outer layer of a two-layer core.
[0006] However, the above-mentioned proposed core rubber compositions have limitations in terms of improvement in durability when the core is struck, and there is a need for further improvement in durability against strikes.
[0007] As a technique for improving various properties such as durability of a rubber composition, Japanese Patent No. 6602150 (Patent Document 10) proposes a technique for incorporating a conjugated diene compound-non-conjugated olefin copolymer into a rubber composition, Japanese Patent No. 6780827 (Patent Document 11) proposes a technique for incorporating a multi-component copolymer containing a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit into a rubber composition, and further, Japanese Patent Laid-Open No. 2012-180456 (Patent Document 12) proposes a technique for incorporating a conjugated diene compound-non-conjugated olefin copolymer and a conjugated diene copolymer into a rubber composition. However, these techniques are intended to improve ozone resistance, weather resistance, crack growth resistance, fracture properties (strength and elongation), etc., and the rubber products are intended for use in tires, conveyor belts, anti-vibration rubber, vibration-isolating rubber, etc., and are not related to the technical field of golf balls, which require required properties such as durability against continuous impacts and hitting feeling, and no mention or suggestion is made of a golf ball core. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] U.S. Patent No. 6,120,390 [Patent Document 2] U.S. Patent No. 6,890,992 [Patent Document 3] U.S. Patent No. 6,332,850 [Patent Document 4] U.S. Patent No. 6,919,395 [Patent Document 5] Patent No. 4020634 [Patent Document 6] Patent No. 6366387 [Patent Document 7] Patent No. 6408811 [Patent Document 8] JP 2020-103339 A [Patent Document 9] Patent No. 6180722 [Patent Document 10] Patent No. 6602150 [Patent Document 11] Patent No. 6780827 [Patent Document 12] JP 2012-180456 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a rubber composition for a golf ball core that can improve durability against cracking during repeated impacts while maintaining the basic properties required of a golf ball, such as flight performance and spin controllability during approach, and a golf ball using the same. [Means for solving the problem]
[0010] As a result of intensive research by the present inventors to achieve the above-mentioned object, it was found that by specifying the multicomponent copolymer of component (b) such that the conjugated diene units contain butadiene units, the non-conjugated olefin units contain ethylene units, and the aromatic vinyl units contain styrene units, and the content of the conjugated diene units in the multicomponent copolymer is 5 mass % or more, the hardness difference in the hardness distribution inside the core can be set to a predetermined value or more while maintaining the desired core hardness, and excellent resistance to cracking during repeated impacts can be achieved, which has led to the present invention.
[0011] The reason for the above-mentioned effect of the present invention is not clear, but is speculated as follows. That is, by crosslinking a multi-component copolymer having a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit with an organic peroxide to a base rubber of a conjugated diene polymer such as polybutadiene, which has been conventionally used for golf ball cores, olefins such as ethylene are efficiently incorporated into the conjugated diene polymer and exist as microcrystals. Then, when the golf ball is struck and deformed, energy is dissipated due to the collapse of intramolecular crystals (microcrystals), which prevents the destruction of the rubber crosslinked structure inside the core, and durability is repeatedly maintained due to the regeneration of the olefin microcrystals after the golf ball is struck.
[0012] The multicomponent copolymer having a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit used in the present invention is a conjugated multicomponent copolymer, and as described above, a crosslinking reaction occurs by an organic peroxide. That is, a non-conjugated multicomponent copolymer such as a conventionally known hydrogenated styrene-based thermoplastic elastomer (SEBS) does not have a double bond in the main chain, so peroxide crosslinking with a conjugated diene polymer is not efficiently performed. As the above-mentioned conjugated multicomponent copolymer used in the present invention, a rubber component containing a multicomponent copolymer containing a conjugated diene unit containing a butadiene unit, a non-conjugated olefin unit containing an ethylene unit, and an aromatic vinyl unit containing a styrene unit is particularly preferable.
[0013] Accordingly, the present invention provides the following rubber composition for a golf ball core and golf ball. 1. Each of the following components (a) to (c), (a) a conjugated diene polymer, (b) a multicomponent copolymer having conjugated diene units, non-conjugated olefin units, and aromatic vinyl units; and (c) Organic peroxide The conjugated diene unit contains a butadiene unit, the non-conjugated olefin unit contains an ethylene unit, the aromatic vinyl unit contains a styrene unit, and the content of the conjugated diene unit in the multicomponent copolymer is 10~60% by mass and The content of the non-conjugated olefin unit in the multicomponent copolymer is 20 to 75% by mass, and the content of the aromatic vinyl unit in the multicomponent copolymer is 3 to 20% by mass. 1. A rubber composition for a golf ball core. 2. The rubber composition for golf ball cores according to the above item 1, wherein the component (a) is at least one member selected from the group consisting of polybutadiene rubber (BR), styrene-butadiene rubber (SBR), isoprene rubber (IR) and natural rubber (NR). 3. The rubber composition for golf ball cores according to the above item 2, wherein the component (a) is polybutadiene rubber (BR). 4. A rubber composition for golf ball cores as described in any one of 1 to 3 above, wherein the content of the conjugated diene units in the multicomponent copolymer is 15 to 50 mass %, the content of the non-conjugated olefin units in the multicomponent copolymer is 45 to 75 mass %, and the content of the aromatic vinyl units in the multicomponent copolymer is 10 to 20 mass %. 5 The multi-component copolymer of component (b) is a copolymer polymerized by a gadolinium metallocene complex catalyst. 4 2. The rubber composition for a golf ball core according to claim 1 . 6 Furthermore, the above-mentioned 1 to 3 containing an α,β-unsaturated carboxylic acid and / or a metal salt thereof as the component (d) 5 2. The rubber composition for a golf ball core according to claim 1 . 7 The above 1 to 3, wherein the ratio of the component (b) to the total amount of the component (a) and the component (b) is 5% by mass or more. 6 2. The rubber composition for a golf ball core according to claim 1 . 8 In the vulcanized molded product of the rubber composition, the difference in hardness between the surface and the center of the vulcanized molded product is 15 or more in JIS-C hardness. 7 2. The rubber composition for a golf ball core according to claim 1 . 9 A golf ball having a core made of one or more layers and a cover made of one or more layers covering the core, wherein at least one layer of the core is 8 2. A golf ball formed from the rubber composition according to claim 1. 10 In the internal hardness distribution of the core, the difference in hardness between the surface and the center of the core is 15 or more in JIS-C hardness. 9 The golf ball described herein. 11. The golf ball according to 9 or 10 above, wherein the ball has a compression hardness (amount of deformation) of 2.10 to 2.40 mm when compressed at a speed of 10 mm / s at a temperature of 23±1°C from an initial load of 98 N (10 kgf) to a final load of 1275 N (130 kgf). Effect of the Invention
[0014] According to the rubber composition for golf ball core of the present invention, when the rubber composition is used as the core of a golf ball, the specific structure of the rubber cross-linked structure inside the core can prevent damage to the gore when the golf ball is hit, thereby improving durability. [Brief description of the drawings]
[0015] [Figure 1] 1 is a graph showing the relationship between the amount of deflection and durability of the ball in each of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will now be described in further detail. The rubber composition for golf balls of the present invention is characterized by containing the following components (a) to (c): (a) a conjugated diene polymer, (b) a multicomponent copolymer having conjugated diene units, non-conjugated olefin units, and aromatic vinyl units; and (c) Organic peroxide
[0017] The conjugated diene polymer of the component (a) is not particularly limited, but specific examples include polybutadiene rubber (BR), styrene butadiene rubber (SBR), isoprene rubber (IR), natural rubber (NR), etc. These may be used alone or in combination of two or more.
[0018] As the conjugated diene polymer, it is preferable to use polybutadiene rubber (BR). Details of the polybutadiene rubber (BR) are as follows.
[0019] The polybutadiene preferably has 60% or more, preferably 80% or more, more preferably 90% or more, and most preferably 95% or more of cis-1,4-bonds in its polymer chain. If the proportion of cis-1,4-bonds in the bonds in the polybutadiene molecule is too small, the resilience may decrease.
[0020] The content of 1,2-vinyl bonds in the polybutadiene is usually 2% or less, preferably 1.7% or less, and more preferably 1.5% or less in the polymer chain. If the content of 1,2-vinyl bonds is too high, the resilience may decrease.
[0021] The polybutadiene has a Mooney viscosity (ML 1+4 (100°C)) is preferably 20 or more, more preferably 30 or more, and the upper limit is preferably 120 or less, more preferably 100 or less, and even more preferably 80 or less. Mooney viscosity is an industrial viscosity index (JIS K 6300) measured with a Mooney viscometer, which is a type of rotational plasticity meter, and is expressed as the unit symbol ML. 1+4 (100°C) is used. M is Mooney viscosity, L is large rotor (L type), 1+4 is preheating time of 1 minute, rotor rotation time of 4 minutes, and indicates that the measurement was performed under the condition of 100°C.
[0022] The polybutadiene that can be used is one synthesized using a rare earth element catalyst or a Group VIII metal compound catalyst.
[0023] The component (b) is a multicomponent copolymer having conjugated diene units, non-conjugated olefin units, and aromatic vinyl units. This multicomponent copolymer is the multicomponent copolymer described in Japanese Patent No. 6780827 and is described as follows:
[0024] <Conjugated diene unit> The multicomponent copolymer contains a conjugated diene unit. The conjugated diene unit is a structural unit derived from a conjugated diene compound as a monomer. Since the multicomponent copolymer can be polymerized using a conjugated diene compound as a monomer, it has excellent crosslinking properties compared to copolymers polymerized using a non-conjugated diene compound such as the well-known EPDM. Therefore, the multicomponent copolymer also has the advantage of being able to further improve the mechanical properties of rubber compositions and rubber products produced using the same. The conjugated diene compound preferably has a carbon number of 4 to 8. Specific examples of the conjugated diene compound include 1,3-butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene. From the viewpoint of effectively improving the breaking performance of a rubber product using the resulting multicomponent copolymer, the conjugated diene compound as a monomer of the multicomponent copolymer preferably contains at least one selected from the group consisting of 1,3-butadiene and isoprene, more preferably consists of at least one monomer selected from the group consisting of 1,3-butadiene and isoprene, and even more preferably consists of only 1,3-butadiene. In other words, the conjugated diene unit in the present multicomponent copolymer preferably contains at least one structural unit selected from the group consisting of 1,3-butadiene units and isoprene units, more preferably consists of at least one structural unit selected from the group consisting of 1,3-butadiene units and isoprene units, and even more preferably consists of only 1,3-butadiene units.
[0025] In addition, the multicomponent copolymer preferably has a cis-1,4 bond content of 50% or more in the entire conjugated diene units. When the cis-1,4 bond content of the entire conjugated diene units is 50% or more, high-strength structures such as molecular chain orientation and elongated crystals are likely to occur, so that the fracture performance of rubber products using the obtained multicomponent copolymer can be effectively improved. From the same viewpoint, the multicomponent copolymer more preferably has a cis-1,4 bond content of 70% or more in the entire conjugated diene units, further preferably 80% or more, and particularly preferably 90% or more. Such a multicomponent copolymer having a high cis-1,4 bond content in the entire conjugated diene units can be obtained by using a conjugated diene compound, a non-conjugated olefin compound, and an aromatic vinyl compound as monomers. On the other hand, the vinyl bond (1,2 vinyl bond, 3,4 vinyl bond, etc.) content in all the conjugated diene units is preferably 30% or less, more preferably 15% or less, even more preferably 10% or less, and particularly preferably 6% or less. Also, the trans-1,4 bond content in all the conjugated diene units is preferably 30% or less, more preferably 15% or less, and even more preferably 10% or less. The contents of cis-1,4 bonds, trans-1,4 bonds and vinyl bonds can be determined from the integral ratios based on the results of 1H-NMR and 13C-NMR measurements.
[0026] The conjugated diene compound may be used alone or in combination of two or more kinds. That is, the multicomponent copolymer may contain one kind of conjugated diene unit alone or may contain two or more kinds. The content of the conjugated diene unit is preferably 5% by mass or more of the entire multicomponent copolymer, more preferably 10% by mass or more, and even more preferably 15% by mass or more. The content of the conjugated diene unit is preferably 80% by mass or less of the entire multicomponent copolymer, more preferably 60% by mass or less, and even more preferably 50% by mass or less. If the content of the conjugated diene unit exceeds 80% by mass of the entire multicomponent copolymer, the effect of the conjugated diene unit becomes too large, and the non-conjugated olefin is not effectively incorporated into the (a) conjugated diene polymer, failing to achieve the intended improvement in durability. If the content is less than 5% by mass, the efficiency of peroxide crosslinking with the (a) conjugated diene polymer decreases, resulting in the non-conjugated olefin not being efficiently incorporated and poor durability.
[0027] <Non-conjugated olefin unit> The multicomponent copolymer contains a non-conjugated olefin unit. The non-conjugated olefin unit is a constituent unit derived from a non-conjugated olefin compound as a monomer. The non-conjugated olefin compound preferably has 2 to 10 carbon atoms. Specific examples of the non-conjugated olefin compound include α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene, and heteroatom-substituted alkene compounds such as vinyl pivalate, 1-phenylthioethene, and N-vinylpyrrolidone. The non-conjugated olefin compound as a monomer of the multicomponent copolymer is preferably an acyclic non-conjugated olefin compound from the viewpoint of further reducing the crystallinity of the resulting multicomponent copolymer and further improving the weather resistance of rubber compositions and tires using such a multicomponent copolymer, and the acyclic non-conjugated olefin compound is more preferably an α-olefin, even more preferably an α-olefin containing ethylene, and particularly preferably composed of ethylene alone. In other words, the non-conjugated olefin unit in the multicomponent copolymer is preferably an acyclic non-conjugated olefin unit, and the acyclic non-conjugated olefin unit is more preferably an α-olefin unit, even more preferably an α-olefin unit containing an ethylene unit, and particularly preferably composed of ethylene alone.
[0028] The non-conjugated olefin compound may be used alone or in combination of two or more kinds. That is, the multicomponent copolymer may contain one type of non-conjugated olefin unit alone or may contain two or more types. The content of non-conjugated olefin units is preferably more than 20% by mass and less than 90% by mass of the entire multicomponent copolymer. If the content of the non-conjugated olefin unit exceeds 90% by mass of the entire multipolymer, the effect of the non-conjugated olefin unit becomes too large, and the efficiency of peroxide crosslinking with (a) the conjugated diene polymer decreases, resulting in inefficient incorporation of the non-conjugated olefin and poor durability. If the content of the non-conjugated olefin unit is less than 20% by mass, the non-conjugated olefin is not incorporated in an effective amount into (a) the conjugated diene polymer, failing to achieve the intended improvement in durability. The content of the non-conjugated olefin unit is preferably from 30 to 85% by mass, more preferably from 40 to 80% by mass, and further preferably from 45 to 75% by mass.
[0029] <Aromatic vinyl unit> The multicomponent copolymer contains an aromatic vinyl unit. The aromatic vinyl unit is a structural unit derived from an aromatic vinyl compound as a monomer. The aromatic vinyl compound has a vinyl group directly bonded to an aromatic ring, and preferably has 8 to 10 carbon atoms. Specific examples of the aromatic vinyl compound include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, o-ethylstyrene, m-ethylstyrene, and p-ethylstyrene. The aromatic vinyl compound as a monomer of the multicomponent copolymer preferably contains styrene, and more preferably consists of styrene, from the viewpoint of further reducing the crystallinity of the resulting multicomponent copolymer and further improving the weather resistance of rubber compositions and tires using such a multicomponent copolymer. In other words, the aromatic vinyl unit in the multicomponent copolymer preferably contains a styrene unit, and more preferably consists of a styrene unit. Incidentally, the aromatic ring in the aromatic vinyl unit is not included in the main chain of the copolymer unless it is bonded to an adjacent unit.
[0030] The aromatic vinyl compounds may be used alone or in combination of two or more kinds. That is, the multicomponent copolymer may contain one type of aromatic vinyl unit alone or two or more types. The content of the aromatic vinyl unit is 3 to 30% by mass of the entire multicomponent copolymer. If the content of the aromatic vinyl unit is less than 3% by mass or more than 30% by mass, the length of the non-conjugated olefin portion of the copolymer cannot be suppressed, and durability improvement derived from the non-conjugated olefin crystals is not achieved. The content of the aromatic vinyl unit is preferably 3 to 30% by mass of the entire multicomponent copolymer, more preferably 5 to 25% by mass, and even more preferably 10 to 20% by mass.
[0031] The number of types of monomers in the above-mentioned multicomponent copolymer is not particularly limited, as long as the multicomponent copolymer contains a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit. The multicomponent copolymer may have other structural units other than the conjugated diene unit, the non-conjugated olefin unit, and the aromatic vinyl unit. From the viewpoint of obtaining the desired effect, the content of other structural units is preferably 30% by mass or less of the whole multicomponent copolymer, more preferably 20% by mass or less, and even more preferably 10% by mass or less, and it is particularly preferable that they are not contained, that is, the content is 0% by mass.
[0032] The multicomponent copolymer is a multicomponent copolymer containing at least one kind of conjugated diene unit, one kind of non-conjugated olefin unit, and one kind of aromatic vinyl unit. From the viewpoint of obtaining favorable breaking characteristics, the multicomponent copolymer is preferably a polymer obtained by polymerizing at least one kind of conjugated diene compound, one kind of non-conjugated olefin compound, and one kind of aromatic vinyl compound as monomers. The multicomponent copolymer is more preferably a terpolymer consisting of only one type of conjugated diene unit, one type of non-conjugated olefin unit, and one type of aromatic vinyl unit, and even more preferably a terpolymer consisting of only 1,3-butadiene units, ethylene units, and styrene units. Here, the term "one type of conjugated diene unit" includes conjugated diene units having different bonding modes.
[0033] A multicomponent copolymer contains conjugated diene units, non-conjugated olefin units, and aromatic vinyl units, and one of its major characteristics is that the main chain is composed only of a non-cyclic structure. If the main chain has a cyclic structure, the breaking properties (especially the breaking elongation) are reduced. Note that NMR is used as the main measuring means to confirm whether the main chain of a multicomponent copolymer has a cyclic structure or not. Specifically, if no peaks derived from the cyclic structure present in the main chain (for example, peaks appearing at 10 to 24 ppm for three- to five-membered rings) are observed, this indicates that the main chain of the multicomponent copolymer is composed only of a non-cyclic structure. Furthermore, as will be described below, the multicomponent copolymer can be synthesized in one reaction vessel, i.e., one-pot synthesis, and can be produced by a simplified process.
[0034] The multicomponent copolymer preferably has a polystyrene-equivalent weight average molecular weight (Mw) of 10,000 to 10,000,000, more preferably 100,000 to 9,000,000, and even more preferably 150,000 to 8,000,000. When the multicomponent copolymer has an Mw of 10,000 or more, the mechanical strength required for a rubber product can be sufficiently ensured, and when the Mw is 10,000,000 or less, high workability can be maintained. The weight average molecular weight and molecular weight distribution are determined by gel permeation chromatography (GPC) using polystyrene as a standard substance.
[0035] The chain structure of the multicomponent copolymer is not particularly limited and can be appropriately selected depending on the purpose. For example, when the conjugated diene unit is A, the non-conjugated olefin unit is B, and the aromatic vinyl unit is C, the multicomponent copolymer can be a block copolymer having a structure such as Ax-By-Cz (x, y, and z are integers of 1 or more), a random copolymer having a structure in which A, B, and C are randomly arranged, a tapered copolymer in which the above random copolymer and a block copolymer are mixed, or an alternating copolymer having a structure such as (ABC)w (w is an integer of 1 or more). In addition, the multicomponent copolymer may have a structure (linear structure) in which the conjugated diene unit, the non-conjugated olefin unit, and the aromatic vinyl unit are linearly linked, or may have a structure (branched structure) in which at least one of the conjugated diene unit, the non-conjugated olefin unit, and the aromatic vinyl unit is linked by forming a branched chain. In addition, when the multicomponent copolymer has a branched structure, the branched chain can also be bi- or multi-component (i.e., the branched chain can include at least two of the conjugated diene unit, the non-conjugated olefin unit, and the aromatic vinyl unit). Therefore, among the multicomponent copolymers, the multicomponent copolymers having a branched structure with bi- or multi-component branched chains can be clearly distinguished from conventional graft copolymers in which the trunk chain and the side chain are formed of one type of unit that is different.
[0036] The production method of the multicomponent copolymer, the polymerization process, the production conditions of the polymerization catalyst used, etc. can be those described in the specification of Japanese Patent No. 6780827. It is preferable that the multicomponent copolymer is polymerized by a gadolinium metallocene complex catalyst.
[0037] In addition, other rubbers such as ethylene propylene diene rubber (EPDM) may be blended as rubber components other than the rubber components (a) and (b) above, provided that the proportion of the other rubber components is 20% by mass or less, preferably 10% by mass or less, and more preferably 5% by mass or less, based on the total rubber.
[0038] Next, the component (c) is an organic peroxide, and it is particularly preferable to use an organic peroxide with a 1-minute half-life temperature of 110 to 185°C as this organic peroxide. Examples of such organic peroxides include dicumyl peroxide (NOF Corp.'s "Percumyl D"), 2,5-dimethyl-2,5-di(t-butylperoxy)hexane (NOF Corp.'s "Perhexa 25B"), and di(2-t-butylperoxyisopropyl)benzene (NOF Corp.'s "Perbutyl P"), and dicumyl peroxide can be preferably used. Other commercially available products include "Perhexa C-40", "Nyper BW", "Peroyl L" (all NOF Corp.'s), or Luperco 231XL (Atochem). These may be used alone or in combination of two or more.
[0039] The amount of the (c) component blended is preferably 0.1 parts by mass or more, and more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the rubber components (hereinafter simply referred to as the "rubber components") of the (a) and (b) components, and the upper limit is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less.
[0040] Furthermore, the rubber composition may contain an α,β-unsaturated carboxylic acid and / or a metal salt thereof as component (d).
[0041] The carbon number of the α,β-unsaturated carboxylic acid is preferably 3 to 8, and specific examples thereof include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, and fumaric acid. Specific examples of the metal of the unsaturated carboxylic acid include zinc, sodium, magnesium, calcium, and aluminum, and zinc is particularly preferred. Therefore, zinc acrylate is the most preferred co-crosslinking agent.
[0042] The amount of component (d) is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of the rubber components (a) and (b) above, and the upper limit is preferably 65 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 55 parts by mass or less. If the amount is less than the above range, the ball will be too soft and have poor resilience, and if the amount is more than the above range, the ball will be too hard, resulting in a poor shot feeling, brittleness, and poor durability.
[0043] The co-crosslinking agent of component (d) preferably has an average particle size of 3 to 30 μm, more preferably 5 to 25 μm, and even more preferably 8 to 15 μm. If the average particle size of the co-crosslinking agent is less than 3 μm, it is likely to aggregate in the rubber composition, and the reactivity between the acrylic acids increases, while the reactivity between the rubber components decreases, so that the resilience of the golf ball may not be sufficient. If the average particle size of the co-crosslinking agent exceeds 30 μm, the co-crosslinking agent particles become too large, and the properties of the resulting golf balls vary widely.
[0044] In addition to the above-mentioned components (a) to (c) and, if necessary, component (d), various additives such as fillers, antioxidants, organic sulfur compounds, and water may be blended as long as they do not impair the effects of the present invention.
[0045] As the filler, for example, zinc oxide, barium sulfate, calcium carbonate, etc. can be suitably used. These may be used alone or in combination of two or more. The amount of the filler to be mixed may be preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component. The upper limit of the amount to be mixed may be preferably 100 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 40 parts by mass or less, per 100 parts by mass of the rubber component. If the amount to be mixed is too large or too small, it may not be possible to obtain the appropriate mass and suitable resilience.
[0046] The antioxidant is not particularly limited, and examples thereof include phenol-based antioxidants such as 2,2-methylenebis(4-methyl-6-tertbutylphenol), 4,4-butylidenebis(3-methyl-6-tertbutylphenol), and 2,2-methylenebis(4-ethyl-6-tertbutylphenol). Commercially available products include Nocrac NS-6, Nocrac NS-30, and Nocrac NS-5 (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.). These may be used alone or in combination of two or more. The amount of the antioxidant is not particularly limited, and is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.0 parts by mass or less, more preferably 0.7 parts by mass or less, and even more preferably 0.4 parts by mass or less, relative to 100 parts by mass of the rubber component. If the amount is too large or too small, the appropriate core hardness gradient may not be obtained, and suitable resilience, durability, and low spin effect during full shots may not be obtained.
[0047] The organic sulfur compound is not particularly limited, and examples thereof include thiophenols, thionaphthols, diphenyl polysulfides, halogenated thiophenols, and metal salts thereof. Specific examples include zinc salts of pentachlorothiophenol, pentafluorothiophenol, pentabromothiophenol, parachlorothiophenol, and the like, diphenyl polysulfide having 2 to 4 sulfur atoms, dibenzyl polysulfide, dibenzoyl polysulfide, dibenzothiazoyl polysulfide, dithiobenzoyl polysulfide, and the like. These may be used alone or in combination of two or more. Among them, the zinc salt of pentachlorothiophenol and / or diphenyl disulfide can be preferably used.
[0048] The amount of the organic sulfur compound is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the rubber component, and the upper limit is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less. If the amount of the organic sulfur compound is too large, the hardness of the hot molded product of the rubber composition may become too soft, while if the amount is too small, improvement in resilience may not be expected.
[0049] Water can be blended into the rubber composition, and there is no particular restriction on the water used, which may be distilled water or tap water, but it is particularly preferable to use distilled water that does not contain impurities. The amount of water blended is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and the upper limit is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, per 100 parts by mass of the rubber component. If the amount of water blended is too much, the hardness becomes soft and the desired hitting feel, durability, and resilience cannot be obtained, and if the amount blended is too little, the desired core hardness distribution cannot be obtained,
[0050] The core can be produced by vulcanizing and curing a rubber composition containing the above-mentioned components. For example, the rubber composition is kneaded using a kneading machine such as a Banbury mixer or a roll, compression molded or injection molded using a core mold, and the molded body is appropriately heated at a temperature sufficient for the organic peroxide and co-crosslinking agent to act, at about 100 to 200°C for 10 to 40 minutes, to cure the molded body.
[0051] The above-mentioned compounding allows the rubber molded product for a golf ball after vulcanization and hardening to have a hardness gradient with a large difference in hardness between the surface and the center. By using the above-mentioned rubber molded product for a golf ball as a core for a golf ball, it is possible to increase the durability of the golf ball while maintaining its good spin characteristics.
[0052] There are no particular limitations on the center hardness of the core, but it is preferably at least 40, more preferably at least 45, and even more preferably at least 50, in JIS-C standard, and the upper limit is preferably not more than 75, more preferably not more than 70, and even more preferably not more than 65. If the center hardness of the core deviates from the above range, the feel on impact may deteriorate or durability may decrease, and the low spin effect may not be obtained.
[0053] The surface hardness of the core is not particularly limited, but is preferably 65 or more, more preferably 70 or more, and even more preferably 72 or more, and the upper limit is preferably 95 or less, more preferably 90 or less, and even more preferably 88 or less, according to the JIS-C standard. If the surface hardness of the core is too low below the above range, the resilience may be reduced and sufficient flight distance may not be obtained. On the other hand, if the surface hardness of the core is too high above the above range, the hitting feeling may be too hard and the durability against cracking due to repeated impacts may be deteriorated.
[0054] Regarding the hardness distribution of the core, the hardness difference between the surface and the center is sufficiently large. Specifically, the hardness difference between the surface A and the center B of the core is preferably 15 or more in JIS-C hardness, more preferably 20 or more, and even more preferably 25 or more, and the upper limit is preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less. If the hardness difference is too small, the low spin effect at the time of W#1 hit may be insufficient, resulting in a loss of flight distance. On the other hand, if the hardness difference is too large, the initial velocity of the ball when actually hit with a golf ball may be low, resulting in a loss of flight distance, or the durability against cracking due to repeated hits may be poor. Here, the center hardness means the hardness measured at the center of the cross section obtained by cutting the core in half (through the center), and the surface hardness means the hardness measured at the surface (spherical surface) of the core. Also, the JIS-C hardness means the hardness measured with a spring type hardness tester (JIS-C type) specified in JIS K 6301-1975.
[0055] It is also preferable that the hardness gradient of the core be such that the hardness is uniform or increases, rather than decreases, from the center of the core to the surface.
[0056] In addition, the compression hardness (amount of deformation) of the core (heat-molded product) when a final load of 1275N (130kgf) is applied from an initial load of 98N (10kgf) is not particularly limited, but is preferably 2.0mm or more, more preferably 2.3mm or more, and even more preferably 2.5mm or more, and the upper limit is preferably 6.0mm or less, more preferably 5.5mm or less, and even more preferably 5.0mm or less. If it is too large, the core becomes too soft, and the low spin effect is not obtained sufficiently and the resilience may decrease. If it is too small, the low spin effect is not obtained and the hit feeling may become hard.
[0057] The diameter of the core is not particularly limited and depends on the layer structure of the golf ball to be manufactured, but is preferably at least 30 mm, more preferably at least 35 mm, and the upper limit is preferably not more than 41 mm, more preferably not more than 40 mm. If the diameter of the core is outside this range, the initial velocity of the ball may be low, or suitable spin characteristics may not be obtained.
[0058] The rubber composition is preferably used as a core for a golf ball as described above. The golf ball of the present invention preferably has a structure including a core of one or more layers and a cover of one or more layers.
[0059] Next, the one or more layers of the cover that encases the core will be described. There are no particular limitations on the cover material, but any of the various known materials used in golf balls, such as ionomer resins and urethane elastomers, can be used.
[0060] To further reduce the spin rate of the ball, it is particularly preferable to use a highly neutralized ionomer material in the layer adjacent to the core. Specifically, it is preferable to use a material containing the following components (i) to (iv): (i-1) an olefin-unsaturated carboxylic acid binary random copolymer and / or a metal ion neutralized product of an olefin-unsaturated carboxylic acid binary random copolymer, (ii-2) an olefin-unsaturated carboxylic acid-unsaturated carboxylic acid ester ternary random copolymer and / or a metal ion neutralized product of an olefin-unsaturated carboxylic acid-unsaturated carboxylic acid ester ternary random copolymer are blended in a mass ratio of 100:0 to 0:100 to (i) a base resin and (ii) a non-ionomer thermoplastic elastomer are blended in a mass ratio of 100:0 to 50:50 to 100 parts by mass of a resin component, (iii) 5 to 80 parts by mass of a fatty acid and / or a derivative thereof having a molecular weight of 228 to 1500; (ix) 0.1 to 17 parts by mass of a basic inorganic metal compound capable of neutralizing unneutralized acid groups in the above components (i) and (iii). In particular, when using a mixed material of the above components (i) to (ix), it is preferable to use one in which 70% or more of the acid groups are neutralized.
[0061] The material for the outermost layer of the cover is preferably a urethane material, particularly a thermoplastic urethane elastomer.
[0062] Furthermore, one or more cover layers (intermediate layers) may be molded between the layer adjacent to the core and the outermost cover layer. In this case, it is preferable to use a thermoplastic resin such as an ionomer as the intermediate layer material.
[0063] To obtain the cover, for example, a method can be adopted in which a single-layer or multi-layer core of two or more layers previously prepared according to the type of ball is placed in a mold, the mixture is heated, mixed, melted, and injection molded to cover the core with the desired cover. In this case, the cover can be manufactured under conditions that ensure excellent thermal stability, fluidity, and moldability, and the final golf ball has high resilience, a good hitting feel, and excellent abrasion resistance. In addition to the above, the cover can also be formed by, for example, previously forming a pair of hemispherical half cups from the cover material, wrapping the core with the half cups, and pressure molding at 120 to 170°C for 1 to 5 minutes.
[0064] When the cover is a single layer, the thickness can be 0.3 to 3 mm. When the cover is a two-layer, the thickness of the outer cover can be 0.3 to 2.0 mm, and the thickness of the inner cover can be 0.3 to 2.0 mm. There are no particular limitations on the Shore D hardness of each layer (cover layer) constituting the cover, but it is preferably 40 or more, more preferably 45 or more, and the upper limit is preferably 70 or less, more preferably 65 or less.
[0065] A large number of dimples are formed on the surface of the outermost layer of the cover, and the cover may be subjected to various treatments such as priming, stamping, painting, etc.
[0066] The present invention relates to a golf ball in which the above rubber composition is used as a core material for at least one layer. The type of golf ball is not particularly limited as long as it has a core and at least one cover layer. For example, the rubber composition can be used in solid golf balls such as two-piece or three-piece solid golf balls in which a solid core is covered with a cover, and multi-piece golf balls with a three or more layer structure, and also in the core of a thread-wound golf ball in which a thread-wound core is covered with a single-layer or multi-layer cover of two or more layers. EXAMPLES
[0067] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0068] [Examples 1 to 4, Comparative Examples 1 to 4] Using the rubber composition containing polybutadiene as the main component shown in Table 1 below, core compositions were prepared by the rubber blends of Examples 1 to 4 and Comparative Examples 1 to 4, and then vulcanization was carried out at 170°C for 15 minutes to produce cores with a diameter of 38.5 mm.
[0069] [Table 1]
[0070] Details of the above formulation are as follows: Polybutadiene rubber: Product name "BR01" (manufactured by JSR Corporation) Zinc oxide: Trade name "Triple Zinc Oxide" (manufactured by Sakai Chemical Industry Co., Ltd.) Anti-aging agent: Product name "Nocrac NS-6" (phenol-based anti-aging agent: manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) Zinc acrylate: Product name "ZN-DA85S" (85% zinc acrylate / 15% zinc stearate), manufactured by Nippon Shokubai Co., Ltd. ·Organosulfur compounds: Pentachlorothiophenol zinc salt: Wako Pure Chemical Industries, Ltd. Organic peroxide (dicumyl peroxide): Trade name "Percumyl D" (manufactured by NOF Corporation) Water: Distilled water
[0071] The details of each of the copolymers "Copolymers A to C, X, and Y" in Table 1 are as follows.
[0072] ( Copolymer A ) Add 95 g of styrene and 400 mL of toluene to a thoroughly dried 1,000 mL pressure-resistant stainless steel reactor. In a glove box under nitrogen atmosphere, 0.17 mmol of mono(bis(1,3-tert-butyldimethylsilyl)indenyl)bis(bis(dimethylsilyl)amide) gadolinium complex (1,3-[(t-Bu)Me2Si]2C9H5Gd[N(SiHMe2)2]2), 0.187 mmol of dimethylanilinium tetrakis(pentafluorophenyl)borate [Me2NHPhB(C6F5)4], and 1.4 mmol of diisobutylaluminum hydride are charged into a glass vessel, and 40 mL of toluene is added to obtain a catalyst solution. The catalyst solution is added to the pressure-resistant stainless steel reactor and heated to 70°C. Next, ethylene is added to the pressure-resistant stainless steel reactor at a pressure of 1.5 MPa, and 150 mL of a toluene solution containing 27 g of 1,3-butadiene is added to the pressure-resistant stainless steel reactor over 30 minutes, and copolymerization is performed for 6 hours at 70° C. After that, 150 mL of a toluene solution containing 27 g of 1,3-butadiene is added to the pressure-resistant stainless steel reactor over 30 minutes, and copolymerization is performed for another hour at 70° C. Next, 1 mL of a 5% by mass solution of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) (NS-5) in isopropanol is added to the pressure-resistant stainless steel reactor to stop the reaction. Next, the copolymer is separated using a large amount of methanol and vacuum dried at 50° C. to obtain copolymer A.
[0073] ( Copolymer B ) Add 80 g of styrene and 600 mL of toluene to a thoroughly dried 1,000 mL pressure-resistant stainless steel reactor. In a glove box under a nitrogen atmosphere, 0.25 mmol of mono(bis(1,3-tert-butyldimethylsilyl)indenyl)bis(bis(dimethylsilyl)amide) gadolinium complex (1,3-[(t-Bu)Me2Si]2C9H5Gd[N(SiHMe2)2]2), 0.275 mmol of dimethylanilinium tetrakis(pentafluorophenyl)borate [Me2NHPhB(C6F5)4], and 1.1 mmol of diisobutylaluminum hydride are charged into a glass vessel, and 40 mL of toluene is added to prepare a catalyst solution. The catalyst solution is added to the pressure-resistant stainless steel reactor and heated to 70°C. Next, ethylene is charged into the pressure-resistant stainless steel reactor at a pressure of 1.5 MPa, and 80 mL of a toluene solution containing 20 g of 1,3-butadiene is further charged into the pressure-resistant stainless steel reactor over 8 hours, and copolymerization is carried out at 70° C. for a total of 8.5 hours. Next, 1 mL of a 5% by mass solution of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) (NS-5) in isopropanol is added to the pressure-resistant stainless steel reactor to stop the reaction. Next, the copolymer is separated using a large amount of methanol and vacuum dried at 50° C. to obtain copolymer B.
[0074] ( Copolymer C ) Add 15 g of styrene and 300 mL of toluene to a thoroughly dried 1,000 mL pressure-resistant stainless steel reactor. In a glove box under a nitrogen atmosphere, 0.25 mmol of mono(bis(1,3-tert-butyldimethylsilyl)indenyl)bis(bis(dimethylsilyl)amide) gadolinium complex (1,3-[(t-Bu)Me2Si]2C9H5Gd[N(SiHMe2)2]2), 0.275 mmol of dimethylanilinium tetrakis(pentafluorophenyl)borate [Me2NHPhB(C6F5)4], and 1.2 mmol of diisobutylaluminum hydride are charged into a glass vessel, and 40 mL of toluene is added to prepare a catalyst solution. The catalyst solution is added to the pressure-resistant stainless steel reactor and heated to 70°C. Next, ethylene is charged into the pressure-resistant stainless steel reactor at a pressure of 1.5 MPa, and further 500 mL of a toluene solution containing 115 g of 1,3-butadiene is charged into the pressure-resistant stainless steel reactor over 4 hours, and copolymerization is carried out at 70° C. for a total of 5 hours. Next, 1 mL of a 5% by mass solution of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) (NS-5) in isopropanol was added to the pressure-resistant stainless steel reactor to terminate the reaction. Next, the copolymer is separated using a large amount of methanol and vacuum dried at 50° C. to obtain copolymer C.
[0075] ( Copolymer X ) Add 10 g of styrene and 600 mL of toluene to a thoroughly dried 1,000 mL pressure-resistant stainless steel reactor. In a glove box under a nitrogen atmosphere, 0.25 mmol of mono(bis(1,3-tert-butyldimethylsilyl)indenyl)bis(bis(dimethylsilyl)amide) gadolinium complex (1,3-[(t-Bu)Me2Si]2C9H5Gd[N(SiHMe2)2]2), 0.275 mmol of dimethylanilinium tetrakis(pentafluorophenyl)borate [Me2NHPhB(C6F5)4], and 1.4 mmol of diisobutylaluminum hydride are charged into a glass vessel, and 40 mL of toluene is added to prepare a catalyst solution. The catalyst solution is added to the pressure-resistant stainless steel reactor and heated to 70°C. Next, ethylene is charged into the pressure-resistant stainless steel reactor at a pressure of 1.5 MPa, and further 50 mL of a toluene solution containing 5 g of 1,3-butadiene is charged into the pressure-resistant stainless steel reactor over a period of 3 hours, and copolymerization is carried out at 70° C. for a total of 4 hours. Next, 1 mL of a 5% by mass solution of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) (NS-5) in isopropanol is added to the pressure-resistant stainless steel reactor to stop the reaction. Next, the copolymer is separated using a large amount of methanol and vacuum dried at 50° C. to obtain copolymer X.
[0076] ( Copolymer Y ) Add 220 g of styrene and 700 mL of toluene to a thoroughly dried 1,000 mL pressure-resistant stainless steel reactor. In a glove box under a nitrogen atmosphere, 0.3 mmol of mono(bis(1,3-tert-butyldimethylsilyl)indenyl)bis(bis(dimethylsilyl)amide) gadolinium complex (1,3-[(t-Bu)Me2Si]2C9H5Gd[N(SiHMe2)2]2), 0.33 mmol of dimethylanilinium tetrakis(pentafluorophenyl)borate [Me2NHPhB(C6F5)4], and 1.4 mmol of diisobutylaluminum hydride are charged into a glass vessel, and 40 mL of toluene is added to prepare a catalyst solution. The catalyst solution is added to the pressure-resistant stainless steel reactor and heated to 70°C. Next, ethylene is charged into the pressure-resistant stainless steel reactor at a pressure of 1.4 MPa, and copolymerization is carried out at 70° C. for 8 hours. Next, 1 mL of a 5% by mass solution of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) (NS-5) in isopropanol is added to the pressure-resistant stainless steel reactor to stop the reaction. Next, the copolymer is separated using a large amount of methanol and vacuum dried at 50° C. to obtain copolymer Y.
[0077] For each of the "copolymers A to C, X, and Y," the contents (mass%) of ethylene, styrene, and butadiene are measured and evaluated by the following method. <Ethylene, styrene, butadiene content> The content of ethylene, styrene, and butadiene in each of the copolymers A to C, X, and Y is 1 The results are shown in Table 2.
[0078] [Table 2]
[0079] Core cross-sectional hardness For each of the above-mentioned examples and comparative examples, the cross-sectional hardness of the surface and center of the core having a diameter of 38.5 mm is measured by the following method. (1) Core surface hardness At a temperature of 23±1°C, the needle of a hardness tester is set perpendicular to the surface of the spherical core, and the surface of the core is randomly measured at four points using the JIS-C hardness scale. The average of these measurements is taken as the measurement value for one ball, and the average of three cores is calculated. The measurements are shown in Table 4. (2) Core cross-sectional hardness The core is cut into a flat surface so that the cross section passes through the center of the core, and at a temperature of 23±1°C, the needle of a hardness tester is set perpendicular to the above-mentioned flat cross section, and the hardness is measured with a JIS-C hardness tester at the center of the hemispherical core and at positions every 2 mm from the center toward the surface, and this is taken as the measurement value for one ball, and the average of three cores is calculated. The measured values are shown in Table 4.
[0080] Compression hardness of core and ball The core and ball are compressed at a speed of 10 mm / s at a temperature of 23±1°C. The compression hardness (deformation) (mm) of the core and ball is measured from an initial load of 98 N (10 kgf) to a final load of 1,275 N (130 kgf), and the average value of 10 pieces is calculated.
[0081] Formation of the cover (middle layer and outermost layer) Next, using an injection molding die, the intermediate layer material (ionomer resin material) shown in Table 3 is injection molded around the surface of the core to form an intermediate layer with a thickness of 1.3 mm and a Shore D hardness of 64. Next, using another injection molding die, the outermost layer material (urethane resin material) shown in Table 2 is injection molded around the intermediate layer-coated sphere to form an outermost layer with a thickness of 0.8 mm and a Shore D hardness of 40.
[0082] [Table 3]
[0083] Details of the blended ingredients in the above table are as follows. "Himilan 1706", "Himilan 1557" and "Himilan 1605": Ionomer resins manufactured by Dow Mitsui Polychemicals "TPU": "Pandex", a product name of DIC Covestro Polymer, an ether-type thermoplastic polyurethane with a Shore D hardness of 40 "Polyethylene wax": Product name "Sanwax 161P" (manufactured by Sanyo Chemical Industries, Ltd.) · Isocyanate compound: 4,4'-diphenylmethane diisocyanate
[0084] The impact durability of the resulting golf balls was evaluated by the following method, and the results are shown in Table 4.
[0085] durability The durability of the balls is evaluated using an ADC Ball COR Durability Tester manufactured by Automated Design Corporation, USA. This test machine has the function of shooting a golf ball with air pressure and then colliding it continuously with two metal plates placed in parallel. The speed of incidence on the metal plates is set to 43 m / s. The number of shots required for the golf ball to break is measured, and the average value of the measured values for 10 golf balls is calculated. An index is also calculated when the average number of times the ball of Comparative Example 1 broke is set to 1.00 (reference value), and is shown in Table 4.
[0086] [Table 4]
[0087] Based on the data in Table 4, the relationship between ball hardness (i.e., the amount of deflection of the ball under a given load) and durability performance in Comparative Examples 1 and 2, which used only high-cis polybutadiene rubber as the polymer component of the rubber composition, is shown by a straight line in Figure 1. Examples 1 and 2 are examples that contain equal amounts of "Polymer A," a multicomponent copolymer of a conjugated diene compound, a non-conjugated olefin, and an aromatic vinyl, and the relationship between ball hardness and durability performance in these examples is shown by a dashed line in Figure 1. In Figure 1, the dashed line is located on the higher durability index side compared to the straight line, indicating that durability performance is improved.
[0088] In Examples 3 and 4, "Polymer B" and "Polymer C" were added instead of "Polymer A", and durability was greater than or equal to a straight line, demonstrating an improvement effect.
[0089] On the other hand, in Comparative Example 3 (example in which "Polymer X" is added) and Comparative Example 4 (example in which "Polymer Y" is added), the curves are almost on a straight line, indicating that no effect of improving durability is observed.
Claims
1. Each of the following components (a) to (c): (a) a conjugated diene polymer, (b) a multicomponent copolymer having conjugated diene units, non-conjugated olefin units, and aromatic vinyl units; and (c) Organic peroxide the conjugated diene units include butadiene units, the non-conjugated olefin units include ethylene units, and the aromatic vinyl units include styrene units; the content of the conjugated diene units in the multicomponent copolymer is 10 to 60% by mass, the content of the non-conjugated olefin units in the multicomponent copolymer is 20 to 75% by mass, and the content of the aromatic vinyl units in the multicomponent copolymer is 3 to 20% by mass.
2. 2. The rubber composition for golf ball cores according to claim 1, wherein said component (a) is at least one selected from the group consisting of polybutadiene rubber (BR), styrene-butadiene rubber (SBR), isoprene rubber (IR) and natural rubber (NR).
3. 3. The rubber composition for golf ball cores according to claim 2, wherein said component (a) is polybutadiene rubber (BR).
4. A rubber composition for golf ball cores as described in any one of claims 1 to 3, wherein the content of the conjugated diene units in the multicomponent copolymer is 15 to 50 mass %, the content of the non-conjugated olefin units in the multicomponent copolymer is 45 to 75 mass %, and the content of the aromatic vinyl units in the multicomponent copolymer is 10 to 20 mass %.
5. 5. The rubber composition for golf ball cores according to claim 1, wherein the multi-component copolymer (b) is a copolymer polymerized by a gadolinium metallocene complex catalyst.
6. 6. The rubber composition for a golf ball core according to claim 1, further comprising an α,β-unsaturated carboxylic acid and / or a metal salt thereof as component (d).
7. 7. The rubber composition for golf ball cores according to claim 1, wherein the proportion of component (b) based on the total amount of components (a) and (b) is 5% by mass or more.
8. 8. The rubber composition for golf ball cores according to claim 1, wherein a vulcanized molded product of said rubber composition has a hardness difference between the surface and the center of said vulcanized molded product of said rubber composition of 15 or more in terms of JIS-C hardness.
9. A golf ball having a core consisting of one or more layers and a cover consisting of one or more layers covering the core, wherein at least one layer of the core is formed from the rubber composition according to any one of claims 1 to 8.
10. 10. The golf ball of claim 9, wherein the core has an internal hardness distribution such that the difference in hardness between the surface and the center of the core is 15 or more in JIS-C hardness.
11. The golf ball of claim 9 or 10, wherein the compression hardness (amount of deformation) of the ball when compressed at a speed of 10 mm / s at a temperature of 23±1°C from an initial load of 98 N (10 kgf) to a final load of 1275 N (130 kgf) is 2.10 to 2.40 mm.
Citation Information
Patent Citations
Vacuum switch
JP1986080722A
Method for dyeing fiber product of polyester fiber / cotton mixture by jet dyeing machine
JP1988066387A
Forming method for rubber or plastic cable connecting section
JP1989008811A
Solid golf ball
JP2001178851A
Golf ball and its manufacturing method
JP2005013455A